Pengaruh Lingkungan terhadap Masyarakat - Tamaulina Br. Sembiring; Khairia Shiva Namira; Fatimah Nadratul Hakim; Ezy Pratama; Muhammad Delfy Zakaria; Armansyah (PT PUSTAKA CENDEKIA GROUP, 2024)
People’s lives are greatly influenced by the environment, both Physical and social. This journal discusses three dimensions of environmental infkuence on society: social , economy, and health. The aim of this study is to study how the environment changes, both caused by natural factors and human activities, affect people’s quality of life. According to this research, environmental damage such as air pollution, deforestation, and climate change can worsen social and economy conditions and threaten public health. Otherwise, healthy environment and well managed benefits society in various aspects of life.